Intercultural communication competence integration in English Language Teaching in Japan and the Philippines - Faramarz Samifanni (Universitas Syiah Kuala, 2026)
This study explores the integration of Intercultural Communicative Competence (ICC) within English Language Teaching (ELT) in Japan and the Philippines—two high-context cultures where intercultural awareness is increasingly vital. Anchored in Byram’s (2020) ICC model, a qualitative case study was used. Data were collected through interviews (Philippines) and an online survey (Japan) with open-ended questions from 22 English teachers, evenly divided between a private university in Japan and a private college in the Philippines. Analysis revealed five key themes: student-centered cultural engagement, reasons for utilizing intercultural teaching methods, varied levels of ICC implementation, application of ICC in the learner’s discipline, and application of ICC in multidisciplinary settings. These themes reflect the evolving nature of ICC in ELT and highlight both shared and divergent practices across the two national contexts. Findings show that educators actively strive to embed ICC principles using available resources and personal pedagogical strategies. However, discrepancies and uncertainties persist due to limited institutional support and the absence of cohesive curricular frameworks. Despite these challenges, a pedagogical shift toward culturally responsive and learner-centered approaches is evident. To strengthen ICC integration, the study recommends localized curricula, sustained professional development, and robust institutional support to bridge theory and practice. This paper calls for further research on ICC integration in ELT across high-and low-context cultures to deepen understanding and inform context-sensitive strategies. Ultimately, the research contributes to the broader discourse on intercultural education by emphasizing the need to empower educators and enhance learners’ communicative competence in increasingly globalized settings.